Measuring sports performance with mobile applications during the COVID-19 pandemic - Lim, J. (Sport Performance & Science Reports, 2020)
This article aims to share some insights into utilising mobile applications for a strength and conditioning coach looking to conduct remote testing and assessments. As technological advancements have led to increased digitisation within sports, an alternative is to utilise mobile applications to remotely assess an athlete`s current physical performance status and strategically plan for their return to sport when training/competitions resumes. Technological advancements insmartphones have enabled these devices to have inbuilt accelerometers, magnetometers, gyroscopes, global positioningsystems, and high definition cameras of high frame rates andscreen resolutions. Mobile applications have been developed to utilise these sensors and functions to assess an athlete`s physical performance. Furthermore, these applicationsare affordable, portable and more importantly, scientifically validated against the gold-standard laboratory equipment thatare currently inaccessible.